2018
DOI: 10.3390/colloids2030040
|View full text |Cite
|
Sign up to set email alerts
|

Metal Ion Interactions with Crude Oil Components: Specificity of Ca2+ Binding to Naphthenic Acid at an Oil/Water Interface

Abstract: Abstract:On the basis of dynamic interfacial tension measurements, Ca 2+ has been shown specifically to interact with naphthenic acid (NA) at the n-heptane/water interface, consistent with NA adsorption followed by interfacial complexation and formation of a more ordered interfacial film. Optimum concentrations of Ca 2+ and NA have been found to yield lower, time-dependent interfacial tensions, not evident for Mg 2+ and Sr 2+ or for several alkali metal ions studied. The results reflect the specific hydration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 101 publications
(112 reference statements)
2
20
0
Order By: Relevance
“…Sodium carboxylate soap emulsion formation is a saponification-style reaction between long-chain fatty acids and monovalent cations (Na + , K + ) in brine. The formation of solid calcium naphthenate soaps involves complexation-style 2:1 bidentate binding of large molecular weight tetraprotic acids (ARN) to Ca 2+ to give practically insoluble coordination compounds and can be interpreted within the framework of the crystallization theory (Taylor and Hiu 2018).…”
Section: Mechanistic Aspectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sodium carboxylate soap emulsion formation is a saponification-style reaction between long-chain fatty acids and monovalent cations (Na + , K + ) in brine. The formation of solid calcium naphthenate soaps involves complexation-style 2:1 bidentate binding of large molecular weight tetraprotic acids (ARN) to Ca 2+ to give practically insoluble coordination compounds and can be interpreted within the framework of the crystallization theory (Taylor and Hiu 2018).…”
Section: Mechanistic Aspectsmentioning
confidence: 99%
“…Therefore, Mg 2+ has a lower tendency to complex with ARN and will barely participate in the formation of an interfacial film (Bertelli et al 2014). In contrast to the weakly soluble coordination compounds formed by Ca 2+ , Mg 2+ tends to form uncoordinated, water-soluble ionic species (Taylor and Hiu 2018). The solubility product of calcium naphthenate is much lower than that of magnesium naphthenate; thus, calcium naphthenate has a greater tendency to exists as a solid precipitate (Simon et al 2012).…”
Section: Calcium Naphthenate Soap Scalementioning
confidence: 99%
“…Tissue samples were collected from animal groups exposed to Norwegian oil in seawater and examined under the microscope and accumulation and toxicity studies of the two synthesized monoaromatic compounds showed morphological abnormalities in such beings, highlighting the dangerousness and spread of the oil in the system of living BEINGS (SØRENSEN et al, 2019). Also, there are many underlying factors responsible for the effects of crude oil and its induced abiotic stresses on the composition of stressed plants, which are poorly understood and require much study (ODUKOYA et al, 2019;OLARANONT et al, 2018;TAYLOR et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Metals can be dissolved in crude oils by formation of complexes with indigenous NA [10]. Being a source of contamination, these metal naphthenates will significantly affect the crude oil quality.…”
Section: Introductionmentioning
confidence: 99%